2022
DOI: 10.1039/d2sc03505g
|View full text |Cite
|
Sign up to set email alerts
|

An iron(ii)-based metalloradical system for intramolecular amination of C(sp2)–H and C(sp3)–H bonds: synthetic applications and mechanistic studies

Abstract: A catalytic system for intramolecular C(sp2)–H and C(sp3)–H amination of substituted tetrazolopyridines has been successfully developed. The amination reactions are developed using an iron-porphyrin based catalytic system. It has been...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 57 publications
(99 reference statements)
1
16
0
1
Order By: Relevance
“…Fe–porphyrin–nitrene species are known to possess a triplet ground state, ,,,, which was also verified with the current complexes derived from 1 – 6 at the DFT-B3LYP level of theory (Table S1). In the following discussion, we will initially present the electronic structure investigation of the Fe–porphyrin–nitrene species 1-Sul and 2-Sul followed by a generalization for all of the complexes, 1-Sul to 6-Sul .…”
Section: Results and Discussionsupporting
confidence: 68%
“…Fe–porphyrin–nitrene species are known to possess a triplet ground state, ,,,, which was also verified with the current complexes derived from 1 – 6 at the DFT-B3LYP level of theory (Table S1). In the following discussion, we will initially present the electronic structure investigation of the Fe–porphyrin–nitrene species 1-Sul and 2-Sul followed by a generalization for all of the complexes, 1-Sul to 6-Sul .…”
Section: Results and Discussionsupporting
confidence: 68%
“…Notably, in recent years, Pro fessor Chattopadhyay's group demonstrated that tetrazole can be employed as an effective nitrene precursor 10 for the intra molecular C(sp 2 )-H amination via iridiumcatalyzed electro cyclization, 11 ironcatalyzed C(sp 3 )-H amination and C(sp 2 )-H amination via a radical mechanism (Scheme 1, D). 12,13 Pro fessor Chattopadhyay remarked: "After that, we were keen to develop a method for intermolecular amination reaction using tetrazole as nitrene precursor to access 2pyridylsub stituted benzylamine. In order to establish suitable reaction…”
Section: Literature Coverage Synformmentioning
confidence: 99%
“…In 2018, Chattopadhyay et al reported the Ir-catalyzed intramolecular transannulation/C(sp 2 )−H amination of 1,2,3,4-tetrazoles. 11 In this process, the denitrogenation of 1,2,3,4-tetrazole occurs at 130 °C by the combination of [Cp*IrCl 2 ] 2 and AgSbF 6 . Thereafter, Mn-porphyrin and Feporphyrin were successively developed by Chattopadhyay for nitrene transfer reactions with 1,2,3,4-tetrazoles (Scheme 1b).…”
mentioning
confidence: 99%